Suppressive effects of morphine injected into the ventral bed nucleus of the stria terminalis on the affective, but not sensory, component of pain in rats. (8th December 2017) - Maruyama, Chikashi; Deyama, Satoshi; Nagano, Yusuke; Ide, Soichiro; Kaneda, Katsuyuki; Yoshioka, Mitsuhiro; Minami, Masabumi
Abstract: Pain is a complex experience with both sensory and affective components. Clinical and preclinical studies have shown that the affective component of pain can be reduced by doses of morphine lower than those necessary to reduce the sensory component. Although the neural mechanisms underlying the effects of morphine on the sensory component of pain have been investigated extensively, those influencing the affective component remain to be elucidated. The bed nucleus of the stria terminalis (BNST) has been implicated in the regulation of various negative emotional states, including aversion, anxiety and fear. Thus, this study aimed to clarify the role of the ventral part of the BNST (vBNST) in the actions of morphine on the affective and sensory components of pain. First, the effects of intra‐vBNST injections of morphine on intraplantar formalin‐induced conditioned place aversion (CPA) and nociceptive behaviors were investigated. Intra‐vBNST injections of morphine reduced CPA without affecting nociceptive behaviors, which suggests that intra‐vBNST morphine alters the affective, but not sensory, component of pain. Next, to examine the effects of morphine on neuronal excitability in type II vBNST neurons, whole‐cell patch‐clamp recordings were performed in brain slices. Bath application of morphine hyperpolarized type II vBNST neurons. Thus, the suppressive effects of intra‐vBNST morphine on pain‐induced aversion may be due to its inhibitory effects on neuronal excitability in type II vBNST neurons. These results suggest that the vBNST is a key brain region involved in the suppressive effects of morphine on the affective component of pain. Abstract : Possible neuronal mechanisms for suppressive effects of morphine on pain‐induced aversion. Pain stimulation induces aversive responses by activating type II BNST neurons (1), then increasing the inhibitory input to the VTA‐projecting type III BNST neurons (2), thereby suppressing the excitatory control on VTA dopaminergic neurons (3, 4). Morphine may suppress pain‐induced aversion by restoring the excitatory control on VTA dopaminergic neurons via the inhibition of type II BNST neurons (5).